Antioxidant and anti-advanced glycation end products formation properties of palmatine - Sharma Mridula; Wardah Siddiqui Masroor; Mellinnda Xavier; Tan Wen Hui; Hor Kuan Chan; Kavita Chirara; Okechukwu Patrick Nwabueze (GarVal Editorial Ltda., 2021)
Context: Oxidative stress and formation of advanced glycation end products (AGEs), due to glycation of proteins, lipids and nucleic acids are characteristic in diabetic patients. Palmatine, a protoberberine alkaloid bioactive isolated from Coscinium fenestratum (CF) stem extract, which previously has shown to possess antidiabetic and antioxidant properties and to be able to protect the kidney and liver in a STZ-diabetic induced rat model. Aims: To evaluate the in vitro and in vivo antioxidant and anti-AGE activity of palmatine. Methods: In vitro and in vivo studies were conducted to measure radical scavenging, reducing power, inhibition of lipid peroxidation, carbonyl trapping and metal ion chelation. In vitro antiglycation activity was done using bovine serum albumin-methylglyoxal (BSA-MGO), bovine serum albumin - glucose (BSA-GLU) and glycated hemoglobin. In vivo antioxidant and antiglycation activity were used to evaluate liver and kidney extracted from STZ-induced diabetic rat after treatment with palmatine. Results: The results showed palmatine blocked the formation of AGE as shown by the results of BSA-GLU, BSA-MGO, glycated hemoglobin and inhibited the free radicals generated by DPPH, nitric oxide, hydrogen peroxide, lipid peroxidation, FRAP and metal ion chelating. It was able to stimulate in vivo the activity of catalase, super oxide dismutase and glutathione peroxidase. Conclusions: Palmatine possess antioxidant and antiglycation properties, the mechanism of action seems to be via the blockage of free radical formation, decreasing of reactive carbonyl. Further research is ongoing to determine the effect of palmatine on glyoxalase 1 and aldose reductase pathway and interaction with receptor for AGE.